2022
DOI: 10.1113/jp283244
|View full text |Cite
|
Sign up to set email alerts
|

In vivo low‐intensity magnetic pulses durably alter neocortical neuron excitability and spontaneous activity

Abstract: Magnetic brain stimulation is a promising treatment for neurological and psychiatric disorders. However, a better understanding of its effects at the individual neuron level is essential to improve its clinical application. We combined focal low‐intensity repetitive transcranial magnetic stimulation (LI‐rTMS) to the rat somatosensory cortex with intracellular recordings of subjacent pyramidal neurons in vivo. Continuous 10 Hz LI‐rTMS reliably evoked firing at ∼4–5 Hz during the stimulation period and induced d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 76 publications
3
8
0
Order By: Relevance
“…In the acute stimulation group, cortical regions directly beneath the coil showed prominent increases in c-Fos density compared to sham, suggesting that 10 Hz LI-rTMS excites neurons within the induced e-field. Our interpretation is supported by previous electrophysiological experiments showing that 10 Hz LI-rTMS triggers action potentials and increases neuronal firing in the barrel cortex (S1) during stimulation 36 . However, in the period immediately after stimulation, there is electrophysiological evidence for both increases and decreases in neuronal activity: Boyer et al 36 found a reduced neuronal firing rate 10–20 min post-stimulation in the barrel cortex, decreasing neuronal excitability, while Tang et al 37 found that LI-rTMS lowered action potential thresholds in vitro in motor cortical neurons, increasing neuronal excitability.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the acute stimulation group, cortical regions directly beneath the coil showed prominent increases in c-Fos density compared to sham, suggesting that 10 Hz LI-rTMS excites neurons within the induced e-field. Our interpretation is supported by previous electrophysiological experiments showing that 10 Hz LI-rTMS triggers action potentials and increases neuronal firing in the barrel cortex (S1) during stimulation 36 . However, in the period immediately after stimulation, there is electrophysiological evidence for both increases and decreases in neuronal activity: Boyer et al 36 found a reduced neuronal firing rate 10–20 min post-stimulation in the barrel cortex, decreasing neuronal excitability, while Tang et al 37 found that LI-rTMS lowered action potential thresholds in vitro in motor cortical neurons, increasing neuronal excitability.…”
Section: Discussionsupporting
confidence: 89%
“…Our interpretation is supported by previous electrophysiological experiments showing that 10 Hz LI-rTMS triggers action potentials and increases neuronal firing in the barrel cortex (S1) during stimulation 36 . However, in the period immediately after stimulation, there is electrophysiological evidence for both increases and decreases in neuronal activity: Boyer et al 36 found a reduced neuronal firing rate 10–20 min post-stimulation in the barrel cortex, decreasing neuronal excitability, while Tang et al 37 found that LI-rTMS lowered action potential thresholds in vitro in motor cortical neurons, increasing neuronal excitability. The different experimental preparations (in vivo vs. in vitro ) make the results hard to compare, and in our study we saw increased c-Fos density in both motor and somatosensory cortices with acute LI-rTMS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The authors concluded that cryptochrome was required for the magnetosensitivity of the neurons, which was consistent with ROS production by activated cryptochrome [222]. In a recent study, the team showed that LI-rTMS (10 mT and 10 Hz) evoked neuronal firing during the stimulation period and induced durable attenuation of synaptic activity and spontaneous firing in cortical neurons of rats in vivo [223].…”
Section: Oscillating Magnetic Field 231 Low-frequencymentioning
confidence: 75%
“…To gain a better understanding of how rTMS affects the brain, custom miniature coils have been developed that deliver focal low-intensity (LI) magnetic stimulation ranging between 1 and 150 mT to the rodent brain [ 85 , 102 , 103 ]. These coils were first used in ephrin-KO mice to attempt to increase neuronal activity and repair abnormal topography [ 104 ].…”
Section: Tms As a Methods To Increase Activity And Compensate For Los...mentioning
confidence: 99%